Nanomaterial-based sensors and strategies for heavy metal ion detection - Xu, Xiaoyu; Yang, Shouzhi; Wang, Yuning; Qian, Kun (Green Analytical Chemistry, 2022)
•Focused on the nanomaterial based sensors for heavy metal ions detection.•An overview of the nano-sensors coupled with mass spectrometry, colorimetry, electrochemistry, surface-enhanced Raman scattering and fluorescence.•Summarized the analytical performances, applications and further challenges of the metal-ion sensors. As one of the most serious toxic contaminants, heavy metal ions have severely threatened the living environment and biological system. Accurate and rapid detection of toxic metal ions is indispensable, urging the necessity of fabricating sensors with low cost, easy-to-operate, and high sensitivity. Numerous recent innovations in material science have reenergized this field and led to the emergence of well-defined nano-sensors with diverse structures and functions. Specifically, noble metal nanoparticles, porous nanomaterials, and semiconductors have been applied in sensor construction, coupled with analytical tools such as mass spectrometry, colorimetry, electrochemistry, surface-enhanced Raman scattering, and fluorescence. This review overviews the latest nanomaterials-based heavy metal ions sensors and focuses on their analytical performances, applications, and challenges.